2018
DOI: 10.1080/00207454.2018.1424152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of olfactory function between neuromyelitis optica and multiple sclerosis

Abstract: Olfactory deficits are common in both NMO and MS. However, the neuroanatomical features related to olfactory deficits differ greatly between the two diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, the association of olfactory dysfunction with neuroimmunological diseases was shown in different studies (38). In a recent MRI study the OF of multiple sclerosis and neuromyelitis optica spectrum disorder was compared (39). It was shown that the neuroanatomical features related to olfactory deficits differ between the two diseases, i.e., the same symptom is based on different pathomechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association of olfactory dysfunction with neuroimmunological diseases was shown in different studies (38). In a recent MRI study the OF of multiple sclerosis and neuromyelitis optica spectrum disorder was compared (39). It was shown that the neuroanatomical features related to olfactory deficits differ between the two diseases, i.e., the same symptom is based on different pathomechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the control group represents healthy individuals without any neurologic disorders and/or diseases. The full list of the included studies is available in the reference section [ 1 , 3 , 6 8 , 13 , 14 , 16 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…They have also done so using different tools including but not limited to Sniffin’ Sticks test [ 9 ], the University of Pennsylvania Smell Identification Test (UPSIT) [ 10 ], the Brief Smell Identification Test (B-SIT) [ 11 ], and the Quick Smell Identification Test (Q-SIT) [ 12 ]. Such studies also lack coherence regarding the prevalence they report, with numbers ranging from 20% to 40% [ 13 ]. It is crucial to study olfactory dysfunction as it plays a major role in diminishing one’s quality of life [ 6 ], and also because there is growing evidence that the degree to which MS patients present with olfactory problems can be used as a potential prognostic factor [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The right orbitofrontal cortex volume in NMO patients with dysosmia was higher than that dysosmia in MS patients. However, the volume of gray matter decreased in the right parahippocampal gyrus and piriform layer in patients with MS ( Li et al, 2018 ), suggesting that the mechanisms of olfactory disorders in NMO and MS may be different.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that olfactory bulb volume reduction also exists in patients with NMOSD olfactory disorders ( Zhang et al, 2015 ). Li et al (2018) compared NMO and MS patients with olfactory disorders and demonstrated that olfactory bulb volume and right orbitofrontal lobe volume in patients with NMO were significantly lower than those in patients with MS. Olfactory disorders in patients with NMOSD and with MS are associated with olfactory damage, but the mechanism of olfactory disorders remains unclear for both. Improved understanding of olfactory-related structure and function will assist better in distinguishing NMOSD from MS.…”
Section: Introductionmentioning
confidence: 99%